Kebijakan Publik dan Pendidikan Islam: Analisis Konsep dan Implementasi dalam Sistem Pendidikan Nasional - Muhamad Rifa; Jesi Novita Sari; Auna Nouri; Luthfi Khoirul Umam; Syafiq Ubaidila (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This article examines the concept of public policy and Islamic education policy, as well as their implementation within Indonesia’s national education system. Public policy serves as a strategic instrument employed by the government to address societal issues and achieve national development goals, including those in the educational sector. Within this framework, Islamic education policy represents an integral component of public educational policy that aims not only to develop intellectual competencies but also to cultivate moral, spiritual, and religious values among learners. This study employs a qualitative descriptive approach through literature review and document analysis of relevant academic sources concerning public policy and Islamic education in Indonesia. The findings indicate that Islamic education has been institutionally integrated into the national education system through madrasahs, pesantren (Islamic boarding schools), Islamic higher education institutions, and the inclusion of Islamic Religious Education in public schools. The implementation of Islamic education policy is reflected in curriculum integration, institutional strengthening, teacher competency development, and the utilization of digital technology in educational processes. Nevertheless, several challenges remain, including disparities in educational quality across regions, limited educational facilities and infrastructure, and the uneven adoption of digital learning technologies. Therefore, stronger collaboration among government institutions, educational organizations, and society is required to enhance the effectiveness of Islamic education policies and improve the overall quality of national education. The study concludes that Islamic education policy plays a significant role in fostering competent, ethical, and religiously grounded citizens while supporting the broader objectives of Indonesia’s national education system.